2009
DOI: 10.1007/s00011-009-0079-6
|View full text |Cite
|
Sign up to set email alerts
|

sTNFR-1 is an early inflammatory marker in community versus institutionalized elderly women

Abstract: Our results demonstrate that being institutionalized has an impact on levels of inflammatory markers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 29 publications
1
11
0
1
Order By: Relevance
“…In our study, even though IL-6 plasma levels were low and sTNFR1 levels were high, there was no impairment of muscle function, grip strength, or gait velocity test performance related to these altered levels. Our results agree with the study of Coelho et al (2010) [7] , who reported an increase in sTNFR1 levels in elderly community dwellers with no impact of handgrip strength. The present study findings indicate that changes in inflammatory cytokines occur at a cellular level before loss of muscle strength and deterioration on functional performance, that is, the adverse repercussions related to the high levels of Inflammatory mediators may become apparent in the long term.…”
Section: Inflammatory Mediators and Physical Function In Community Elsupporting
confidence: 82%
“…In our study, even though IL-6 plasma levels were low and sTNFR1 levels were high, there was no impairment of muscle function, grip strength, or gait velocity test performance related to these altered levels. Our results agree with the study of Coelho et al (2010) [7] , who reported an increase in sTNFR1 levels in elderly community dwellers with no impact of handgrip strength. The present study findings indicate that changes in inflammatory cytokines occur at a cellular level before loss of muscle strength and deterioration on functional performance, that is, the adverse repercussions related to the high levels of Inflammatory mediators may become apparent in the long term.…”
Section: Inflammatory Mediators and Physical Function In Community Elsupporting
confidence: 82%
“…This finding demonstrates that high levels of sTNFR1 represent lowgrade inflammation present in nonagenarian elderly, which could negatively influence the training capacity of these individuals. In a recent study, Coelho et al found that concentrations of sTNFR1 were higher in elderly subjects when compared to younger subjects living in the same community and that these concentrations correlated with the age of volunteers [35].…”
Section: Discussionmentioning
confidence: 98%
“…Values of less than 31 cm were considered indicative of depleted muscle mass and correlated with incapacity. 16 The AMMI and body composition assessments were performed using Dual Energy X-Ray Absorptiometry (DXA, Discovery A Hologic model). These assessments were conducted in the Laboratório Bioquímico e Densitométrico (Biochemistry and Densitometry Laboratory) (LABDEN) of the Universidade Tecnológica Federal do Paraná (Federal University of Technology of Paraná).…”
Section: Sarcopenia Indicatorsmentioning
confidence: 99%